Phosphoinositide 3-kinase p110δ promotes lumen formation through enhancement of apico-basal polarity and basal membrane organization - Peng, Juan (Nat Commun, 2015)
Signaling triggered by adhesion to the extracellular matrix plays a key role in the spatial orientation of epithelial polarity and formation of lumens in glandular tissues. Phosphoinositide 3-kinase signaling in particular is known to influence the polarization process during epithelial cell morphogenesis. Here, using Madin-Darby canine kidney epithelial cells grown in 3D culture, we show that the p110δ isoform of phosphoinositide 3-kinase colocalizes with focal adhesion proteins at the basal surface of polarized cells. Pharmacological, siRNA- or kinase-dead mediated inhibition of p110δ impair the early stages of lumen formation, resulting in inverted polarized cysts, with no laminin or type IV collagen assembly at cell/extracellular matrix contacts. p110δ also regulates the organization of focal adhesions and membrane localization of dystroglycan. Thus, we uncover a previously unrecognized role for p110δ in epithelial cells in the orientation of the apico-basal axis and lumen formation.